A brief stylistic and thematic approach to Ánxel Fole’s poetry - García López, José Ángel (Madrygal. Revista de Estudios Gallegos, 2014)
This essay deals with a little study over some stylistic features and tematic themes seen in the poetry of Galician writer Ánxel Fole. In addition, we offer a poem which is not included in Fole’s complete published works to this day.
Keywords: poetry; Spanish literature; Galician literature; Ánxel Fole.